Psychological well-being in adolescents from divorced families: A literature review on key dimensions and influencing factors - Derima Putri, Bunga; Soekandar Ginanjar , Adriana (Universitas Mercu Buana Yogyakarta, 2025)
This literature review examined the psychological well-being of adolescents who experienced parental divorce, along with the factors that influenced it. Using the PRISMA method, 17 articles were analyzed from the database of Scopus, PubMed, Taylor & Francis, and Google Scholar. The review found that the six dimensions of psychological well-being showed varied results. Some studies reported improvements in autonomy and a sense of purpose in life, while others found that adolescents continued to struggle in these areas. In terms of the positive relations with others, relationships with fathers were generally associated with negative outcomes, whereas peer relationships tended to provide positive support. Findings related to environmental mastery and personal growth also varied across studies. In contrast, self-acceptance generally increased over time. Several internal factors were identified as being protective for adolescents’ psychological well-being, including religiosity, adaptive coping strategies, self-control, and resilience. External factors that contributed positively included social support, a secure attachment style, higher levels of education, and better socio-economic status. The interaction between these internal and external factors appeared to enhance adolescents’ adaptability and support their overall psychological well-being. Based on the findings of this review, several practical implications were proposed to support adolescents from divorced families. Recommended interventions included resilience-based training, programs to strengthen social support, school-based mindfulness activities, attachment-based family therapy (ABFT), and the adolescent adaptation pilot program to parental divorce (AAPPD). These interventions play a crucial role in enhancing adolescents' psychological well-being. Keyword: Psychological well-being, adolescents, divorced families